Tubulin and tau: Possible targets for diagnosis of Parkinson’s and Alzheimer’s diseases - Salama, Mohamed; Shalash, Ali; Magdy, Alshimaa; Makar, Marianne; Roushdy, Tamer; Elbalkimy, Mahmoud; Elrassas, Hanan; Elkafrawy, Passent; Mohamed, Wael Mohamed Yousef; Abou Donia, Mohamed B. (Public Library of Science, 2018)
Neurodegenerative diseases including Alzheimer’s disease (AD) and Parkinson’s disease (PD) are characterized by progressive neuronal loss and pathological accumulation of some proteins. Developing new biomarkers for both diseases is highly important for the early diagnosis and possible development of neuro-protective strategies. Serum antibodies (AIAs) against neuronal proteins are potential biomarkers for AD and PD that may be formed in response to their release into systemic circulation after brain damage. In the present study, two AIAs (tubulin and tau) were measured in sera of patients of PD and AD, compared to healthy controls. Results showed that both antibodies were elevated in patients with PD and AD compared to match controls. Curiously, the profile of elevation of antibodies was different in both diseases. In PD cases, tubulin and tau AIAs levels were similar. On the other hand, AD patients showed more elevation of tau AIAs compared to tubulin. Our current results suggested that AIAs panel could be able to identify cases with neuro-degeneration when compared with healthy subjects. More interestingly, it is possible to differentiate between PD and AD cases through identifying specific AIAs profile for each neurodegenerative states.